Teachers’ Challenges in Classroom Management in Teaching English at SMKN 8 Bulukumba - Akbar Maulana; Munir Munir; Syarifah Farahdiba (State University of Makassar, 2024)
Challenges of teachers in classroom management teaching English in SMKN 8 Bulukumba. All foreign language teachers face challenges in teaching and managing their classes. The objectives of this study are: (1) To investigate the teachers and their challenges in teaching English in SMKN 8 Bulukumba. (2) To investigate the challenges faced by English teachers in classroom management in SMKN 8 Bulukumba. The subjects of this study are two teachers who teach at SMKN 8 Bulukumba. In terms of teachers' difficulties in managing classrooms, teachers are faced with students' lack of motivation to learn English and students who disrupt the class while studying. About some of these challenges, it seems that there are many challenges in teaching and managing lessons when teaching English in the classroom.Keywords: Challenges, Teaching English, Classroom Management.